2022
DOI: 10.1001/jamainternmed.2022.2168
|View full text |Cite
|
Sign up to set email alerts
|

High-Dose Dexamethasone and Oxygen Support Strategies in Intensive Care Unit Patients With Severe COVID-19 Acute Hypoxemic Respiratory Failure

Abstract: IMPORTANCEThe benefit of high-dose dexamethasone and oxygenation strategies vs standard of care for patients with severe acute hypoxemic respiratory failure (AHRF) caused by COVID-19 pneumonia is debated.OBJECTIVES To assess the benefit of high-dose dexamethasone compared with standard of care dexamethasone, and to assess the benefit of high-flow nasal oxygen (HFNO 2 ) or continuous positive airway pressure (CPAP) compared with oxygen support standard of care (O 2 SC). DESIGN, SETTING, AND PARTICIPANTSThis mul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
58
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 97 publications
(70 citation statements)
references
References 40 publications
4
58
0
1
Order By: Relevance
“…Patients with a WHO-OSCI of 5 or higher were not enrolled. Bouadma et al also compared dexamethasone 20 mg daily versus 6 mg daily in patients who required oxygen support or invasive mechanical ventilation [ 20 ]. In this study, high-dose dexamethasone did not significantly improve 60-day survival.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with a WHO-OSCI of 5 or higher were not enrolled. Bouadma et al also compared dexamethasone 20 mg daily versus 6 mg daily in patients who required oxygen support or invasive mechanical ventilation [ 20 ]. In this study, high-dose dexamethasone did not significantly improve 60-day survival.…”
Section: Discussionmentioning
confidence: 99%
“…Would 12 mg be better than 6 mg? Two randomized controlled trials 28,29 did not show a statistically signifi cant benefi t in terms of survival at 28 days in patients who received 12 mg compared with those who received 6 mg. Therefore, 6 mg of dexamethasone is still most commonly given.…”
Section: Low Vs High Dose Of Dexamethasone In Covid-19mentioning
confidence: 95%
“…Other factors related to SARS-CoV-2 infection include the high frequencies of pulmonary emboli and pulmonary infarction, the particular severity and length of ARF that required prolonged mechanical ventilation (12-30 days on average [50]), deep sedation and neuromuscular blockade, and the frequent use of extracorporeal membrane oxygenation [43]. The role of steroid therapy during SARS-CoV-2 infection in the occurrence of bacterial infections is debated [51][52][53][54][55] but has been associated with systemic infections such as invasive aspergillosis [56].…”
Section: Specific Risk In Icumentioning
confidence: 99%
“…Several studies suggested an increase of BSI during SARS-CoV-2 infections, half of which were healthcare-associated [60,73,74]. The potential impact of drug-induced immunosuppression in this increase is still debated [51,52,75].…”
Section: Bacteremiamentioning
confidence: 99%